ANALISIS MANAJEMEN STRATEGI PELESTARIAN DAN PENGEMBANGAN KAWASAN KOTA LAMA SEBAGAI UPAYA MENUJU KAWASAN WISATA BUDAYA DI KOTA SEMARANG - Primadani, Emma; Larasati, Endang; Subowo, Ari (Journal of Public Policy and Management Review, 2013)
Semarang Old City area is a heritage building that should be preserved its existence. His condition is dire. Actually, the government has been implementing conservation and development strategies to revitalize the area. But the strategy is done so that the state government is not unified the Old Town area no change at all. The problems arise: what are the factors enabling and constraining the strategy, and what strategies are used in the preservation and development of the Old Town area in order to be a cultural tourist area in the city of Semarang?Research purposes to describe what are the factors enabling and constraining the conservation strategy and the development of the Old City through the analysis of the strategic environment and to explain what strategy should be taken by the government in managing the Old Town area in order to be a cultural tourist area in the city of SemarangEfforts to address the problem and the purpose of the study used the theory of strategic management using SWOT analysis tool, as well as the litmus test. With descriptive qualitative research design.The results showed that the region lies in the cultural themed segments I and II themed segments on the tour is the Old Town area. For any form of preservation and development must be done in accordance with the regulations that have been made to daaerah Old City of Semarang, but the rules can not be implemented properly by the government. Lack of coordination between related SKPD be one of the factors inhibiting and berpotensinya as an area of cultural tourism is one of the supporters.Suggested the government should be able to restore coordination between SKPD related to the preservation and development of the Old Town area of Semarang.Keywords: Conservation